The Effects of Immunosuppressive Factors on Primary Dendritic Cells from C57BL/6 and CBA Mice - Vasiliy V. Kurilin; Julia N. Khantakova; Valeriy P. Tereschenko; Julia A. Lopatnikova; Irina A. Obleukhova; Sergey V. Sennikov (Journal of Immunology Research)
Introduction. Dendritic cells (DCs) control immune responses by modulating T and B cells towards effector or tolerogenic responses. In this study, we evaluated the effects of different immunosuppressive molecules on the phenotypic and functional characteristics of primary dendritic cells from C57BL/6 and CBA mice. Methods. DCs were derived from bone marrow cells in the presence of rmGM-CSF and rmIL-4. DCs were then treated with different types of immunosuppressive molecules (rmIL-10, rmTGF-β, and BAY 11-7082) and cocultured with syngeneic splenocytes. The amount of CD4+CD25hiFoxP3+ Tregs, IL-10 expression, and proliferation were evaluated. Results. Tolerogenic factors were found to have different effects on DCs C57Bl/6 mice. In C57Bl/6 mice, BAY 11-7082 alone had no effect on the expression of DC maturation molecules (CD80, CD86). Transforming growth factor beta (TGF-β), alone and in combination with BAY 11-7082, reduced the expression of these molecules. Cocultivation of DCs with splenocytes in the presence of TGF-β and BAY 11-7082 favored regulatory T cell (CD4+CD25hiFoxP3+) differentiation and disfavored differentiation of CD4+ T cells producing IL-10. In CBA mice, we found that rmIL-10 and rmTGF-β have a weak effect on maturation of DCs and their functional properties to induce Treg cells and IL-10 production. Conclusion. These results indicate that TGF-β and IL-10 have different effects on the phenotypic and functional characteristics of DCs and that the NF-κB inhibitor, BAY 11-7082, has no synergistic effect on these treatments. In mice with an opposite nature of the immune response, the effects of immunoregulatory cytokines (IL-10 and TGF-b) differ on maturation of dendritic cells.